2018
DOI: 10.1080/13561820.2018.1427051
|View full text |Cite
|
Sign up to set email alerts
|

What did first-year students experience during their interprofessional education? A qualitative analysis of e-portfolios

Abstract: Interprofessional collaboration is an essential approach to comprehensive patient care. As previous studies have argued, interprofessional education (IPE) must be integrated in a stepwise, systematic manner in undergraduate health profession education programmes. Given this perspective, first-year IPE is a critical opportunity for building the foundation of interprofessional collaborative practice. This study aims to explore the first-year students' learning processes and the longitudinal changes in their perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 33 publications
1
25
0
2
Order By: Relevance
“…Ten of the studies did not mention whether the IPE program was supported financially [ 30 , 47 – 49 , 51 , 54 – 58 ]. Finally, in 14 studies, the authors did not state whether any conflicts of interest existed [ 30 , 45 – 51 , 53 – 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ten of the studies did not mention whether the IPE program was supported financially [ 30 , 47 – 49 , 51 , 54 – 58 ]. Finally, in 14 studies, the authors did not state whether any conflicts of interest existed [ 30 , 45 – 51 , 53 – 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Abu‐Rish et al 11 noted this trend has limitations on the development of strategies which target long‐term impact on collaboration. Imafuku et al 12 identified a need to better understand how undergraduates’ perceptions of IPC and their professional identity develop through ongoing participation in IPE. Findings from their study found that first‐year health professional students’ participation in a year‐long IPE programme facilitated students’ understanding of communication/teamwork and identity formation as a collaborative team member 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Imafuku et al 12 identified a need to better understand how undergraduates’ perceptions of IPC and their professional identity develop through ongoing participation in IPE. Findings from their study found that first‐year health professional students’ participation in a year‐long IPE programme facilitated students’ understanding of communication/teamwork and identity formation as a collaborative team member 12 . Despite these many contributions to the field, there remains a gap in our understanding of when and how to incorporate IPE within health professional training 5,13 .…”
Section: Introductionmentioning
confidence: 99%
“…11 However, through interactions with patients, students realized that health professionals also had to gain a better understanding of the patient' s psychosocial needs. 22 It is therefore suggested that medical students may not necessarily be disappointed by CP, but rather expect high CP values from the viewpoints of care providers at the entry level. This may be confirmed by the results of the negative response to the factor, "Team efficiency," especially among students from Gunma University.…”
Section: Discussionmentioning
confidence: 99%